Daylight Robbery - Graham, Elspeth; Illustrated by Newsham, Ian (Pakistan Oxford University Press, 2001)
There's a thief in Duck Green School. Someone has stolen Poppy's ribbons, Buzz's hairband and Mrs Best's scarf. Who could it be? This title introduces the final stage of "Duck Green School" stories to complete the KS1 guided reading series.
Include Color Illustrations